2017
DOI: 10.3389/fmicb.2017.00901
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TGF-β on Treg Cells in Adverse Pregnancy Outcome upon Toxoplasma gondii Infection

Abstract: Toxoplasma gondii (T. gondii) is a ubiquitous intracellular protozoan parasite that causes adverse pregnancy outcomes. Its infection downregulates the Treg cell population and TGF-β level, which may contribute to adverse pregnancy outcomes. TGF-β plays a critical role in Treg cell development, but whether TGF-β treatment can affect the number and function of Treg cells and hence alleviate adverse pregnancy outcomes caused by T. gondii infection remains elusive. In this study, T. gondii-infected pregnant mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…Recently, it is reported that Tregs are suppressed in vitiligo not only on their amounts but also on their function. The polymorphisms of several immunosuppressive genes expressed in Tregs including transcription factor Forkhead box P3 (Foxp3), interleukin‐10 (IL‐10) and transforming growth factor β (TGF‐β) are associated with susceptibility to vitiligo. Moreover, the function of Tregs has been shown impaired in vitiligo patients, with weaker suppressive effect of Tregs on autologous CD8 + T cells and decreased expression level of Foxp3 and cytotoxic T lymphocyte antigen‐4 (CTLA‐4) that induces the anergy of effector T cells .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that Tregs are suppressed in vitiligo not only on their amounts but also on their function. The polymorphisms of several immunosuppressive genes expressed in Tregs including transcription factor Forkhead box P3 (Foxp3), interleukin‐10 (IL‐10) and transforming growth factor β (TGF‐β) are associated with susceptibility to vitiligo. Moreover, the function of Tregs has been shown impaired in vitiligo patients, with weaker suppressive effect of Tregs on autologous CD8 + T cells and decreased expression level of Foxp3 and cytotoxic T lymphocyte antigen‐4 (CTLA‐4) that induces the anergy of effector T cells .…”
Section: Introductionmentioning
confidence: 99%
“…The immune response has been proposed as a critical factor involved in the control of the parasite T. gondii in individuals with acquired toxoplasmosis (11,(15)(16)(17)(18)(19)(24)(25)(26). We previously reported that T. gondii vertical transmission might be related to those cases positive to proinflammatory cytokines such as IFN-γ and negative to the immunoregulatory cytokine TGFβ (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal pregnancy in T. gondii ‐infected mice could be improved by increasing expression of cytotoxic T lymphocyte‐associated antigen‐4 (CTLA‐4) and programmed death 1 (PD‐1) on Treg cells . Using a mouse model, a different group reported that TGF‐β treatment improved the abnormal pregnancy caused by T. gondii infection by increasing Treg differentiation and function via the TGF‐β/Smad3 signalling pathway …”
Section: Protective Immunity Of Toxoplasma Gondii Infection During Prmentioning
confidence: 99%